A Systematic Literature Review: How Mastery of Whole Number Concepts Develops Students' Problem-Solving Skills - Ratih Handayani; Ratu Ilma Indra Putri; Zulkardi; Darmawijoyo (Eksponen, 2026)
Conceptual difficulties and visual representation barriers are often major challenges in learning integers, especially related to understanding negative numbers and mathematical operations such as addition and subtraction. This study aims to identify the problems faced by students in learning integers, evaluate the effectiveness of various teaching methods, and propose innovative approaches to improve students' understanding. The methodology used is a systematic review based on Systematic Literature Review (SLR), by analyzing relevant research articles using PRISMA guidelines. This study examines various learning strategies, such as the use of realistic contexts, innovative visual models, manipulatives, and interactive technology. The results showed that a real-world context- based approach and the use of visual models can significantly improve students' understanding compared to conventional methods. Students who engaged in manipulative-based learning and class discussions also showed better mathematical thinking flexibility. These findings highlight the need for further exploration of the use of real contexts, more innovative visual models, and the application of gamification technology in integer learning. In conclusion, integer learning requires a more innovative approach by integrating realistic contexts, new visual models, and interactive technology. This not only increases student engagement but also supports the development of conceptual and procedural abilities more effectively.